Selective leaching for the recovery of Valuable metals from waste crystalline-silicon solar cells - Chimeddorj, Ganzorig; Urtnasan, Erdenebold; Wang, Jei-Pil (International Journal of Innovative Research and Scientific Studies, 2025)
Due to the rapid expansion of the solar energy market over the past few decades, a large amount of waste from discarded silicon-based solar modules has accumulated, representing a considerable source of recoverable silicon and silver. High-efficiency metal recovery from solar cells in the recycling process is achieved through leaching with sulfuric, hydrochloric, and nitric acids; numerous studies have shown that nitric acid is particularly effective in recovering metals including aluminum, silver, copper, and lead from these cells. The selective leaching of valuable metals from pulverized silicon-based solar cells was examined in this study, employing nitric acid to achieve the dual objective of recovering the leached metals and simultaneously purifying the undissolved silicon fraction to yield high-purity silicon. For the leaching experiments, nitric acid solutions of 1M, 2M, and 3M concentrations were prepared as molar solutions and then treated in an ultrasonic cleaner, which was kept at a constant temperature of 60 °C for the duration of the experiment. The effect of leaching time on the further purification of silicon through selective leaching using a 1M concentration at 60 °C was also investigated. Throughout the duration of the leaching experiments, analysis of the silicon phases within the remaining material following the selective leaching process, with careful consideration given to both the concentration of the leaching agents and the length of the reactions, verified that the metals were effectively removed only after the leaching process had surpassed a 30-minute period. With a purity exceeding 99%, the silicon is of exceptionally high quality, indicating that advanced processing techniques were employed. Silver extraction from the solution was accomplished using copper, a reducing agent, introduced into a silver nitrate solution; this initiated a redox reaction, with varying amounts of copper (0.25, 0.5, 0.75, and 1 gram) added according to stoichiometric calculations based on the reaction between the silver nitrate solution and the solid copper. Silver precipitation occurred at 0.23 and 0.55 grams, respectively, upon the addition of 0.75 and 1.0 grams of copper, which caused the precipitation reaction.